On the Boundedness of Hausdorff Operators on Morrey-Type Spaces - Burenkov, Victor Ivanovich; Liflyand, Elijah (Eurasian Mathematical Journal, 2017)
We give conditions ensuring the boundedness of Hausdorff operators on Morrey-type spaces. Sharpness of the obtained results is studied, and classes of the Hausdorff operators are described for which the necessary and sufficient conditions coincide.